Far migration of an intrauterine contraceptive device from the uterus to the small bowel. Issue 3 (13th March 2022) - Carroll, Alexandria; Paradise, Courtney; Schuemann, Katie; Schellhammer, Shannon Scott; Carlan, Steve J.
Abstract: A sexually active, asymptomatic 44‐year‐old presented for Intrauterine device (IUD) removal that had been in place for 13 years. IUD removal was unsuccessful as the strings could not be located. Imaging revealed an extrauterine IUD and at surgical removal of the abdominal IUD a small bowel perforation requiring bowel resection was required. Uterine perforation is a rare complication of IUD use occurring in approximately 1–1.3 in 1000. Risk factors for perforation include provider inexperience, retroverted uterus, immobile uterus, and myometrial defect from a previous cesarean delivery or myomectomy. Abstract : If women who choose to wear IUDs are taught how to locate the strings through self‐vaginal examination, complications from perforation or expulsion can be reduced. The time to teach is at insertion. This case is an opportunity for quality improvement through proper patient education and best practice teaching message.